Characterization of Listeria monocytogenes isolated from wildlife in central New York. Issue 3 (3rd February 2022) - Chen, Tong; Orsi, Renato H.; Chen, Ruixi; Gunderson, Maureen; Roof, Sherry; Wiedmann, Martin; Childs‐Sanford, Sara E.; Cummings, Kevin J.
Abstract: Background: Listeria monocytogenes ( Lm ) present in farming soil and food‐processing facilities threatens food safety, but little is known about the carriage of Lm by wildlife. Objectives: We estimated the prevalence of faecal Lm shedding among wildlife admitted to a veterinary medical teaching hospital in central New York and characterized a subset of the Lm isolates. Methods: Wildlife samples were collected between May 2018 and December 2019. We characterized the Lm isolates by assessing the growth at three temperatures approximating the body temperatures of reptiles (25°C), mammals (37°C), and birds (42°C) and identifying genotypic characteristics related to transmission and virulence. Results: The apparent prevalence of faecal Lm shedding was 5.6% [18/324; 95% confidence interval (CI), 3.3%–8.6%]. Among 13 isolates that represented two lineages and 11 clonal complexes, three and five isolates were grouped into the same SNP clusters with human clinical isolates and environmental isolates, respectively. However, specific SNP difference data showed that Lm from wildlife was generally not closely related (>22 SNP differences) to Lm from human clinical sources and the food‐processing environment. While the stress response locus SSI‐2 was absent, SSI‐1 was found in four isolates. Virulence genes prfA, plcA, hly, mpl, actA, plcB, inlA, inlB, inlC, inlE, inlH, inlJ, and inlK were present, without any premature stop codons, in all isolates. Virulence loci Listeria pathogenicity island 3 ( LIPI‐3 ) and LIPI‐4, which have been linked to hypervirulence, and inlG were found in four, three, and seven isolates, respectively. Conclusions: Wildlife represents a potential reservoir for genetically diverse and putatively hypervirulent Lm strains. No statistically significant association between growth parameters and hosts was observed. However, compared to lineage I isolates, lineage II isolates showed significantly ( p < 0.05) faster growth at 25°C and significantly slower growth at 42°C, suggesting that wildlife Lm isolates that belong to lineages I and II differ in their ability to grow at 25°C and 42°C. Abstract : We estimated the prevalence of fecal Listeria monocytogenes ( Lm ) shedding among wildlife admitted to a veterinary medical teaching hospital and characterized the isolates. The apparent prevalence of fecal Lm shedding among central New York wildlife was approximately 6%. The Lm isolates had no mutations associated with virulence attenuation and harbored genes associated with hypervirulence; thus, wildlife may be reservoirs or carriers of potentially hypervirulent Lm .